Transcriptome exploration in Leymus chinensis under saline-alkaline treatment using 454 pyrosequencing. - Yepeng Sun (Public Library of Science (PLoS), 2013)
Background Leymus chinensis (Trin.) Tzvel. is a high saline-alkaline tolerant forage grass genus of the tribe Gramineae family, which also plays an important role in protection of natural environment. To date, little is known about the saline-alkaline tolerance of L. chinensis on the molecular level. To better understand the molecular mechanism of saline-alkaline tolerance in L. chinensis, 454 pyrosequencing was used for the transcriptome study. Results We used Roche-454 massive parallel pyrosequencing technology to sequence two different cDNA libraries that were built from the two samples of control and under saline-alkaline treatment (optimal stress concentration-Hoagland solution with 100 mM NaCl and 200 mM NaHCO(3)). A total of 363,734 reads in control group and 526,267 reads in treatment group with an average length of 489 bp and 493 bp were obtained, respectively. The reads were assembled into 104,105 unigenes with MIRA sequence assemable software, among which, 73,665 unigenes were in control group, 88,016 unigenes in treatment group and 57,576 unigenes in both groups. According to the comparative expression analysis between the two groups with the threshold of "log2 Ratio ≥1", there were 36,497 up-regulated unegenes and 18,218 down-regulated unigenes predicted to be the differentially expressed genes. After gene annotation and pathway enrichment analysis, most of them were involved in stress and tolerant function, signal transduction, energy production and conversion, and inorganic ion transport. Furthermore, 16 of these differentially expressed genes were selected for real-time PCR validation, and they were successfully confirmed with the results of 454 pyrosequencing. Conclusions This work is the first time to study the transcriptome of L. chinensis under saline-alkaline treatment based on the 454-FLX massively parallel DNA sequencing platform. It also deepened studies on molecular mechanisms of saline-alkaline in L. chinensis, and constituted a database for future studies.